2020
DOI: 10.1111/acv.12593
|View full text |Cite
|
Sign up to set email alerts
|

Immigration does not offset harvest mortality in groups of a cooperatively breeding carnivore

Abstract: The effects of harvest on cooperatively breeding species are often more complex than simply subtracting the number of animals that died from the group count. Changes in demographic rates, particularly dispersal, could offset some effects of harvest mortality in groups but this is rarely explored with cooperative breeders. We asked whether a cooperatively breeding species known for long-distance dispersal could compensate for the effect of harvest mortality on density by adopting immigrants into the group. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…By contrast, Bassing et al . (2020) found that the proportion of immigrants within groups in a protected population was low and did not change when pack size and offspring recruitment declined after hunting and trapping began. In addition, they documented similarly low immigrant acceptance in a population hunted and trapped at a higher rate.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Bassing et al . (2020) found that the proportion of immigrants within groups in a protected population was low and did not change when pack size and offspring recruitment declined after hunting and trapping began. In addition, they documented similarly low immigrant acceptance in a population hunted and trapped at a higher rate.…”
Section: Resultsmentioning
confidence: 99%
“…Harvest of the Rocky Mountain wolf population began in 2009. Although declines in group size and density have been documented (Ausband et al., 2017; Bassing et al., 2020), we do not know how such declines might affect the reproductive potential of this population, if at all. We estimated and compared several reproductive rates for individuals in both small and large groups using empirical data collected from radio‐collared wolves in Idaho and Yellowstone National Park (YNP), Wyoming, USA during a period of wolf recovery and recolonization (1996–2012).…”
Section: Introductionmentioning
confidence: 78%
“…In North America, areas with open wolf hunting seasons had lower management removals but not lower illegal harvest, and did not result in a pronounced increase in total anthropogenic mortality. Different types of human‐caused mortality can impact not only wolf abundance, but also social patterns, suggesting that conservation planning should consider the potential effects of harvest regulations beyond population sizes (Bassing et al, 2020; Rutledge et al, 2010). Moreover, although carnivores can adapt to humans, there is a strong need to understand and integrate their ecology and management in human‐modified landscapes (Carter & Linnell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of human-caused mortality can impact not only wolf abundance, but also social patterns, suggesting that conservation planning should consider the potential effects of harvest regulations beyond population sizes (Bassing et al, 2020;Rutledge et al, 2010).…”
Section: The Lack Of Clear Influence Of An Open Hunting Season In Totalmentioning
confidence: 99%